Electrical properties of ion gels based on PVDF-HFP applicable as gate stacks for flexible devices - Chae, Kwanbyung; Cuong, Nguyen Duc; Ryu, Shinyoung; Yeom, Dong Il; Ahn, Y. H.; Lee, Soonil; Park, Ji Yong (Current Applied Physics, 2018)
Electrical characteristics of ion gels prepared by loading different amounts of 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([EMIM][TFSI]) in Poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) are investigated and compared with those of ion liquid, [EMIM][TFSI] for possible application as a gate stack for flexible electronic devices. Capacitance and impedance as a function of frequency are measured, which can be well accounted for by a simple circuit model identifying the local device components. The operation of a flexible field effect transistor based on graphene and the ion gel as a top gate stack is also demonstrated.
Keywords: Electrical characteristic; Flexible device; Flexible electronic devices; Function of frequency; Gate stacks; Ion gels; Poly(vinylidene fluoride-co-hexafluoropropylene); Simple circuits; Field effect transistor; Flexible device; Ion gel; Ion liquid; Polymer